PENGARUH PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP STRUKTUR MODAL PADA PERUSAHAAN KONSTRUKSI YANG TERDAFTAR DI BEI PERIODE 2018-2022 - Poetri, Fatma Freska; Maryanti, Sri; Waldelmi, Idel (Komunitas Manajemen Kompetitif, 2024)
The aim of this research is to determine the effect of profitability and company size on the capital structure of construction companies registered in BEI for the 2018-2022 period, through financial ratios as research variables, namely profitability consisting of Return on Assets (ROA), Return on Equity (ROE) and Return on Investment (ROI), company size (SIZE) and capital structure or Debt to Equity Ratio (DER). This research uses secondary data, namely company financial publications via the Indonesia Stock Exchange website (www.idx.co.id). The research results show that by partial data testing, the Profitability variable has a significant effect on the Capital Structure of Construction Companies Registered in BEI for the 2018-2022 period, so H1 is accepted. Partially, the company size variable has no effect on the capital structure of construction companies registered on BEI for the 2018-2022 period, so H2 is rejected. Then the profitability and company size variables simultaneously have a positive and significant effect on the capital structure of construction companies registered with BEI for the 2018-2022 period, so H3 is accepted.